Primer registro de Pseudapanteles dignus (Hymenoptera: Braconidae) como parasitoide de Tuta absoluta (Lepidoptera: Gelechiidae) en el Alto Valle de Río Negro, Argentina - Garrido, Silvina (2017)
The larval endoparasitoid Pseudapanteles dignus (Hymenoptera: Braconidae) is reported for the first time attacking the South American tomato moth Tuta absoluta (Lepidoptera: Gelechiidae) in tomato crops at Alto Valle de Río Negro, being this the most southern report for Argentina. Besides, P dignus diagnosis and parasitism percentage are briefly commented.